AN ANALYSIS OF SPEECH FUNCTION IN ENGLISH CLSSROOM INTERACTION AT SMPN 1 HINAI - Dina Afrianti; Neni Afrida Sari Harahap (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This research deals with speech functions used by teacher and students during reading comprehension session in English Vocational classroom interaction. The objective of this study were (1) to investigate the types of speech function that are used by teacher in English classroom interaction (2) To describe how the speech functions are realized in Mood in English classroom interaction. A descriptive qualitative design was used in the study. The data were collected by recording the utterances of the teacher at SMPN 1 Hinai. The subjects of the study were teacher and students in SMPN 1 Hinai. The data collected by recording the teacher and students utterances in classroom interaction. There were 45 utterances produced of the teacher. The types of speech function that have been found the teacher in the classroomare statement, question, offer and command. Which are question and statement more often used by teacher in classroom interaction.For realization of speech function of teacher and students.there is way that have been found in realization of speech functions of teacher and students, namely, typical utterances mood (congruent). In typical utterances mood, there are four ways that have been found, namely statement realized in declarative mood, offer realized by declarative, then command realized in imperative mood, question realized in interrogative.